PEDAGOG-TALABA HAMKORLIK FAOLIYATI SHAKLLANISHIGA XOS MASALALARNING O‘RGANILISHI - Beknazarova, L.S. (SCIENCE and SOCIETY, 2022)
This article focuses on the theoretical and practical aspects of the study of teacher-student cooperation in the comprehensive implementation of a system of motives and incentives to work effectively for the common good.
Keywords: teacher; student; education; cooperation; problem; research; communication; emotion; interaction